High‐Frequency Trading and Financial Time‐Series Prediction with Spiking Neural Networks. Issue 113 (27th May 2021) - Gao, Kang; Luk, Wayne; Weston, Stephen
Abstract : A novel new method is introduced ‐ "unsupervised spike learning" ‐ which predicts spikes in price time series instead of price movement and direction. Three rewarding high‐frequency trading strategies are developed and backtested by Kang Gao, Wayne Luk, and Stephen Weston.